A foreign body in the heart due to an unusual injury - Harrer, Jan; Holubec, Tomas; Brtko, Miroslav (The Annals of thoracic surgery, 2009)
Penetrating heart injuries are immediate life-threatening situations. We present a case report of a 44-year-old man with a foreign body in his right heart. The injury happened while the man was working with a circular saw 15 months prior to the actual diagnosis. With respect to the size of the foreign body, its close proximity to the right coronary artery, the potential risk of bleeding, embolization, endocarditis or pericarditis, surgical therapy was indicated in spite of the fact that the patient was asymptomatic. The foreign body (a spring-segment of a roller blind) was successfully removed.
Keywords: Metals; kovy; reoperace; penetrující rány; echokardiografie; Wounds, Penetrating; trikuspidální chlopeň; Echocardiography; poranění srdce; mužské pohlaví; srdeční komory; Adult; Postoperative Complications; Reoperation; koronární cévy; koronární angiografie; Coronary Angiography; vyvolaná zástava srdce; Foreign Bodies; Coronary Vessels; Granuloma, Foreign-Body; Heart Arrest, Induced; Humans; Heart Ventricles; Heart Injuries; Tricuspid Valve; cizí tělesa; dospělí; granulom z cizího tělesa; pooperační komplikace; lidé; Male